Plant Lice Species (Suborder: Sternorrhyncha) on Ornamental Plants in Kampal Village and Surrounding Areas - Delia Nurhaliza; Masrianih Masrianih; Manap Trianto; Amalia Buntu; Yulia Windarsih; Lestari MP Alibasyah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Plant lice (Suborder: Sternorrhyncha) are important pests of ornamental plants, capable of causing physical damage and transmitting plant pathogens. These insects pose a significant threat as they can reduce growth, impair physiological functions, and even cause plant death. Their feeding activity affects leaves, stems, and flowers, thereby reducing overall plant health and aesthetic value. Understanding the diversity and host associations of these pests is essential for effective management. This study aimed to identify the species of Sternorrhyncha plant lice present on ornamental plants in Kampal Village, Parigi Moutong, Central Sulawesi. A qualitative descriptive approach was employed, using purposive sampling to collect specimens from different plant parts, including shoots, leaves, flowers, and stems. Observations were recorded and analyzed to determine species composition, host range, and infestation patterns. A total of 25 ornamental plant species belonging to 16 families were observed as host plants. Some plant families, such as Euphorbiaceae, Acanthaceae, Rubiaceae, Palmae, Rutaceae, Araceae, and Agavaceae, were infested by more than one plant louse family, while individual plant species could host multiple louse families simultaneously. Seventeen Sternorrhyncha species were identified, distributed across seven families: Pseudococcidae (6 species), Coccidae (3), Diaspididae (2), Aphididae (2), Margarodidae (2), and Aleyrodidae and Ortheziidae (1 species each). These results provide baseline data on the diversity and distribution of Sternorrhyncha plant lice in Kampal Village. Such information is critical for developing targeted pest management strategies to protect ornamental plants and maintain their health and aesthetic value in residential and cultivated areas.